2009
DOI: 10.1007/s00223-008-9211-9
|View full text |Cite
|
Sign up to set email alerts
|

Intravenous Pamidronate in Osteogenesis Imperfecta Type VII

Abstract: Cyclical intravenous treatment with pamidronate is widely used to treat osteogenesis imperfecta (OI) types I, III, and IV, which are due to dominant mutations affecting collagen type I alpha chains. There is no information about the effects of pamidronate in children with OI type VII, an autosomal-recessive form of OI caused by a mutation in the cartilage-associated protein gene. In this retrospective single-center study, we compared the effects of pamidronate in four girls with OI type VII (age range 3.9-12.7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
3
3
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(27 citation statements)
references
References 19 publications
2
23
0
2
Order By: Relevance
“…The most frequently used approach is intravenous pamidronate, which has been reported to lead to increased lumbar spine bone mineral density and cortical thickness, improvements in vertebral shape, stronger muscles, and better mobility function. A recent study suggests that the effects of intravenous pamidronate treatment are similar in patients with hypomorphic CRTAP mutations as in patients who have OI of similar severity caused by collagen type I mutations [18]. Treatment [12] Nonsense/nonsense F 36 wk 2,435 Died at 3 mo Barnes et al [12] Start codon/frameshift F Term 2,600 Died at 10 mo Barnes et al [12] Splice with intravenous bisphosphonates is clearly beneficial in infants with OI caused by collagen type I mutations, and therefore might reasonably be used in infants with inactivating CRTAP mutations as well.…”
Section: Treatmentmentioning
confidence: 97%
See 1 more Smart Citation
“…The most frequently used approach is intravenous pamidronate, which has been reported to lead to increased lumbar spine bone mineral density and cortical thickness, improvements in vertebral shape, stronger muscles, and better mobility function. A recent study suggests that the effects of intravenous pamidronate treatment are similar in patients with hypomorphic CRTAP mutations as in patients who have OI of similar severity caused by collagen type I mutations [18]. Treatment [12] Nonsense/nonsense F 36 wk 2,435 Died at 3 mo Barnes et al [12] Start codon/frameshift F Term 2,600 Died at 10 mo Barnes et al [12] Splice with intravenous bisphosphonates is clearly beneficial in infants with OI caused by collagen type I mutations, and therefore might reasonably be used in infants with inactivating CRTAP mutations as well.…”
Section: Treatmentmentioning
confidence: 97%
“…In the four adult patients, fractures were rare after puberty, but by then they required wheelchairs for mobility. The four younger patients who received intravenous pamidronate treatment during childhood and adolescence were ambulatory without assistance at the end of puberty [18]. None of the patients with the hypomorphic mutation developed respiratory problems in the postnatal period and none was diagnosed with cardiac or other anomalies.…”
Section: Hypomorphic Mutationmentioning
confidence: 99%
“…In OI type VII, cortical width increased with pamidronate treatment, but trabecular bone volume did not change significantly. 39 The longer-term effects of pamidronate treatment on the bone tissue were evaluated in a longitudinal study of 25 children and adolescents with OI who had received intravenous pamidronate for >4 years. 40 Iliac bone biopsies were performed at treatment start, after 2.7 ± 0.5 years (mean ± SD) and after 5.5 ± 0.7 years of therapy.…”
Section: Effects Of Bisphosphonate Treatment In Oimentioning
confidence: 99%
“…In contrast, experience with BPs in children with various pathologies, such as juvenile osteoporosis, has been limited until recently and most of the current reports refer to small numbers of patients. [83][84][85][86] Following limited early studies, 87,88 several researchers have demonstrated that oral (olpadronate 89,90 and alendronate 91,92 ) or intravenous (pamidronate [93][94][95][96][97][98][99][100][101] and neridronate 102,103 ) BP treatment has a beneficial effect on children with severe OI. 104 In a large non-controlled observational study involving 30 children (aged 3 to 16 years) with severe OI, Glorieux and colleagues demonstrated that the cyclic administration of intravenous pamidronate improved clinical outcomes, decreased the incidence of fractures, reduced bone resorption, increased bone density and the size of vertebral bodies.…”
Section: Treating Osteogenesis Imperfectamentioning
confidence: 99%
“…106 Despite unanswered questions concerning them, BP treatment does appear to have a strong positive effect on the morbidity of severe forms of OI and it seems reasonable to continue the treatment more extensively. 107 These studies [93][94][95][96][97][98][99][100][101][102][103] reported encouraging results and strongly indicate that BPs are useful in the symptomatic treatment of children with severe OI, moreover without serious adverse effects. As with earlier studies these current trials share a common limitation, namely they are all open trials, therefore these favorable results should be confirmed in double-blind controlled studies.…”
Section: Treating Osteogenesis Imperfectamentioning
confidence: 99%